Goal Striving and Well-Being in Sport: The Role of Contextual and Personal Motivation - Healy, L.; Ntoumanis, Nikos; Veldhuijzen van Zanten, J.; Paine, N. (Human Kinetics, 2014)
This investigation sought to clarify mixed results in the literature exploring coach behaviors, basic psychological needs, goal motivation, and well- and ill-being. Regional-level team sport athletes (N = 241) completed questionnaires on the aforementioned variables at the beginning of the season. A subsample (n = 70) provided saliva samples to assess physical ill-being. At the end of the season, athletes (n = 98) reported their goal motivation and attainment. Structural equation modeling demonstrated that coach behaviors were related to needs satisfaction and thwarting, which were related to autonomous and controlled goal motives respectively. Autonomous motives were related to well- and ill-being; controlled motives were only related to ill-being. Over time, only end-of-season autonomous goal motives were related to goal attainment. The findings provide an insight into how coaches can facilitate optimum goal striving and well-being in their athletes.